A randomised controlled trial of periconal eye blockade with or without ultrasound guidance - Najman, I. E. [UNESP]; Meirelles, R.; Ramos, L. B.; Guimaraes, T. C. F.; Nascimento, P. do [UNESP] (Wiley-Blackwell, 2015)
We randomly allocated 129 participants with normal eyes to periconal blockade with (n=69) or without (n=60) ultrasound guidance before cataract surgery. There was no difference in the rates of complication, 1/69 and 0/60, respectively, p=1.0. The rate of intraconal needle placement was 1/69 with ultrasound and 12/60 without ultrasound, a relative risk (95% CI) of 0.07 (0.01-0.55), p<0.0001.